Women Empowerment: Concept Paper - Masvikeni, Tecla; Kasu, Christine, Mary; Mugadza, Gladys (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Women empowerment is the ability to say out views without belittling the other part. Thisinvolves the process of mutual dialogue, negotiation done to meet social needs..Empowerment is the Process on a continuum to raise awareness, capacity building that leadsto greater variety of participation, greater decision making power, control and transformativeaction.